An Analysis of Mercury (Hg) Levels in Face Whitening Cream Circulated at Lueng Putu Market, Bandar Baru District - Razi, T. Khairol (International Conference on Multidisciplinary Research, 2021)
Whitening cream is a type of cosmetics containing various chemical substances that can lighten dark spots on the skin. Prolonged use of whitening cream is claimedto be able to reduce or even eliminate hyperpigmentation on the skin. However, many whitening creams contain mercury which can cause pigmentation with permanent damages on the skin and body. The creams sometimes have no BPOM permission and are sold at a cheap price. This study thus aimed to investigate the presence of Mercury (Hg) in facial whitening creams of two different brands, namely Natural 99 and Collagen Night, circulating at Lueng Putu Market, Bandar Baru District, Pidie Jaya Regency. These brands were selected because they are popular among women living around the Lueng Putu market. This type of research was experimental. Based on the examination of the mercury content in two samples using a positive atomic absorption spectrophotometer method, it was found that there ismercury (Hg) with level of 176.2578 in Sample1 and level of 172.7299 in Sample 2.This concentration exceeds the threshold set by the BPOM RI Number 12 of 2019, which should be no more than 1 mg/kg or 1 mg/L (ppm). It is thus suggested that customers stop using the creamsto avoid their dangerous effects. For detoxification purpose, customers should use skin care products with natural ingredients, such as fruit masks for external treatment, andconsume fruit, vegetables, and more water for internal treatment.Consulting a doctor is highly advised before and after using certain whitening creams. Keywords: Mercury Level, Face Whitening Cream.